MiR‐595 Suppresses the Cellular Uptake and Cytotoxic Effects of Methotrexate by Targeting SLC19A1 in CEM/C1 Cells. Issue 1 (22nd February 2018) - Wang, Shu‐Mei; Sun, Lu‐Lu; Wu, Wan‐Shui; Yan, Dan
Abstract: The human solute carrier family 19 member 1 ( SLC19A1 ) is the gene coding for reduced folate carrier 1 (RFC1). In our previous work, we showed that the miR‐595‐related polymorphism, rs1051296 G>T, which was located in the 3′‐untranslated region (3′‐UTR) of SLC19A1, was associated with high methotrexate (MTX) plasma concentrations in patients with paediatric acute lymphoblastic leukaemia (ALL). This study aimed to investigate the role of miR‐595 in the regulation of SLC19A1 expression and its effects on the cellular uptake and cytotoxicity of MTX in ALL CEM/C1 cells. Luciferase reporter assay was performed to validate SLC19A1 as a miR‐595 target. RFC1 protein expression was determined via Western blotting. Intracellular MTX concentrations were measured by enzyme‐linked immunosorbent assay (ELISA). Cell viability and apoptosis were assessed using Cell Counting Kit‐8 (CCK‐8) assay and flow cytometer, respectively. Compared to the negative control, miR‐595 mimics induced a significant decrease in the relative luciferase activity by binding to the 3′‐UTR of SLC19A1 harbouring the rs1051296 T allele ( p  <   0.01). Treatment of CEM/C1 cells with miR‐595 mimics substantially reduced RFC1 protein expression, intracellular MTX levels, MTX‐induced cytotoxicity and apoptosis rates compared to those of negative control. However, opposite results were observed in cells transfected with a miR‐595 inhibitor. These findings suggested that miR‐595 acts as a phenotypic regulator of MTX sensitivity in CEM/C1 cells by targeting SLC19A1 . This study helped us to understand the mechanisms underlying the variable MTX responses observed in patients with ALL.